Figur Ayub di Yakobus 5:11 Sebagai Simbol Solidaritas Dan Pengharapan Dalam Penderitaan - Jani Jani; Donovan Dugan; Lie Agan (Predica Verbum: Jurnal Teologi dan Misi, 2024)
This article explores the use of the paradigmatic figure Job in James 5:11, focusing on themes of solidarity and hope in the context of suffering. This study adopts a hermeneutic approach to understand how James describes Job as a model of solidarity and hope in the midst of suffering. Analysis of the text of James 5:11 was carried out to capture the linguistic and theological nuances underlying the choice of Job as a symbol of hope. This article also examines the historical and social context of the recipients of James' letter, highlighting how Job's message of perseverance was relevant to their situations. Furthermore, this research is also directed at the spiritual and psychological manifestation of solidarity and hope in Suffering, referring to the story of Job as a reflection of the universal human experience in facing difficulties. Through this, this study provides a deeper understanding of how the figure of Job is used paradigmatically in the Letter of James to inspire and give strength to the early Christian community in the face of suffering. The results show that James not only uses Job as an example of hope, but also as a means to build solidarity among believers in the face of trials. This article provides new insights into how biblical texts can be used to support solidarity and hope amidst adversity. Keywords: Paradigmatic, Job, Solidarity, Hope, Suffering